Improved accuracy of U-series and radiocarbon dating of ostrich eggshell using a sample preparation method based on microstructure and geochemistry: A study from the Middle Stone Age of Northwestern Ethiopia. (1st November 2020) - Loewy, S.L.; Valdes, J.; Wang, H.; Ingram, B.; Miller, N.R.; Medina, K.de la Cruz; Roberts, A.; Yanny, S.; Banner, J.; Feseha, M.; Todd, L.; Kappelman, J.
Abstract: The Middle Stone Age (MSA) is important to studies of human evolution because it witnessed the origin of modern Homo sapiens and its dispersal out of Africa and across the rest of the Old World. Obtaining accurate ages for these and other events that occurred during this time interval is of critical importance. Ostrich eggshell (OES) is commonly found in MSA sites, and OES calcite can be dated by radiocarbon and U-series geochronologic techniques. It is important to understand how both techniques are potentially compromised when the eggshell's pore clusters and intercrystalline microporosity are infilled with younger calcite and/or soil-derived detrital materials. We investigated this question by using high-resolution X-ray computed tomography (HRXCT) to reveal the extent and three-dimensional structure of the pore clusters, and element mapping to evaluate concentrations of detrital elements in modern versus ancient OES within the pore clusters and the crystal (outer) and cone (inner) layers relative to the palisade (central) layer. HRXCT results support earlier findings that OES pores are generally composed of one to several openings on the cone surface that develop into a complex three-dimensional cluster of anastomosing and branching pores that extend through the palisade layer to exit on the crystal surface. These hollow pore clusters provide a considerable total volume for the potential ingress of detrital materials. Element mapping revealed high concentrations of detrital mineral indicator elements (Al, Mg) in ancient relative to modern OES, and in the cone and crystal layers relative to the palisade layer. Within the palisade layer of ancient OES, there are relatively high detrital mineral indicator element concentrations within filled pore clusters. Extracted pore cluster infill from the palisade layer yields significantly higher and more variable concentrations of 232 Th (2, 200-10, 000 ppt) and 238 U (35–54 ppb) relative to the non-porous palisade layer (150–3, 100 ppt 232 Th, and 19–25 ppb 238 U). Based on these results, we developed a mechanical preparation method that combines the removal of the pore cluster infill with the more common removal of the cone and crystal layers. Using this method, U–Th analyses of four OES from an MSA archaeological site in NW Ethiopia yielded a mean age of 75.7±4.7 ka (2 SD). The inclusion of the pore cluster infill with the palisade in a different OES from the same site produced a much younger age of 53±1.2 ka (1 SE). Splits of several of these same OES samples prepared by this new method yield AMS 14 C ages that are beyond the range of 14 C dating (∼50 ka), while ∼60% of the OES analyses of the palisade layer that retained the pore cluster infill yielded much younger ages (27–38 ka). Our results demonstrate that dating OES that retains the pore cluster infill shifts both U–Th and 14 C analyses to younger ages. In order to obtain more precise and accurate ages, we recommend that preparation of OES for both U-series and 14 C dating include the mechanical removal of both the pore cluster infill and the cone and crystal layers in order to more fully account for the incorporation of Th, U, and C from detrital and authigenic minerals within the OES structure. Highlights: HRXCT shows that pore clusters offer a large volume for ingress of contaminants. Cone and crystal and pores of ancient OES can contain detrital/authigenic elements. Incomplete removal of contaminants can produce inaccurate dates that are too young. Mechanical preparation should remove everything but the central palisade layer. Dating the palisade layer only by U-series and 14 C improves accuracy and precision.